(untitled) ("Journal "U". Economy. Management. Finance.", 2021)
The article is devoted to the marketing activities of retail. The author reveals the relevance of the implementation of marketing activities in this industry. And also highlights the features of retail, which are manifested in the course of marketing activities. As a result of the study of the issue of improving the effectiveness of marketing activities in retail, the author identifies such methods as creating a marketing service, launching advertising, and implementing CRM systems. It is noted that these methods will increase the profitability of the business, increase competitiveness.